Tendensi Rasio Profitabilitas Dalam Memproyeksikan Return Saham - Azmi, Shamad Hasanul; Arisyahidin, Arisyahidin; Suwasono, Edy (Prodi Manajemen Fakultas Ekonomi dan Bisnis Universitas Islam Raden Rahmat Malang, 2023)
This study aims to find out how big the profitability ratio is in projecting stock returns for go public companies engaged in the mining sector which are included in the pre-pandemic to post-pandemic LQ45 index for the 2017-2022 period. This study uses a quantitative descriptive method and uses a purposive sampling technique. The analysis technique uses trend analysis. The results of the research and discussion during the study period were that the four profitability ratio indicators (NPM, ROA, ROE, EPS) experienced a positive trend or uptrend and were accompanied by an uptrend on stock returns. This indicates that when the company is successful in generating profits, investors will scramble to buy these shares so that the share price will increase and of course it will create a greater return value that can be felt by shareholders. And when the company has the ability to generate profits, the greater the potential stock returns that will occur.